Micropollutants as internal probe compounds to assess UV fluence and hydroxyl radical exposure in UV/H2O2 treatment. (1st May 2021) - Wünsch, Robin; Mayer, Carina; Plattner, Julia; Eugster, Fabienne; Wülser, Richard; Gebhardt, Jens; Hübner, Uwe; Canonica, Silvio; Wintgens, Thomas; von Gunten, Urs
Highlights: UV fluence and OH exposure were calculated from abatements of two micropollutants The abatement of other micropollutants was predicted within ±20 % The model allowed estimations of k OH and k UV of co-existing micropollutants A sensitivity analysis showed limited effect of analytical errors if probe compounds were abated > 50% Abstract: Organic micropollutants (MPs) are increasingly detected in water resources, which can be a concern for human health and the aquatic environment. Ultraviolet (UV) radiation based advanced oxidation processes (AOP) such as low-pressure mercury vapor arc lamp UV/H2 O2 can be applied to abate these MPs. During UV/H2 O2 treatment, MPs are abated primarily by photolysis and reactions with hydroxyl radicals ( OH), which are produced in situ from H2 O2 photolysis. Here, a model is presented that calculates the applied UV fluence ( H calc ) and the OH exposure ( C T OH, calc ) from the abatement of two selected MPs, which act as internal probe compounds. Quantification of the UV fluence and hydroxyl radical exposure was generally accurate when a UV susceptible and a UV resistant probe compound were selected, and both were abated at least by 50 %, e.g., iopamidol and 5-methyl-1H-benzotriazole. Based on these key parameters a model was developed to predict the abatement of other MPs. The prediction of abatement was verified in various waters (sand filtrates of rivers Rhine and Wiese, and a tertiary wastewater effluent) and at different scales (laboratory experiments, pilot plant). The accuracy to predict the abatement of other MPs was typically within ±20 % of the respective measured abatement. The model was further assessed for its ability to estimate unknown rate constants for direct photolysis ( k UV, MP ) and reactions with OH ( k OH, MP ). In most cases, the estimated rate constants agreed well with published values, considering the uncertainty of kinetic data determined in laboratory experiments. A sensitivity analysis revealed that in typical water treatment applications, the precision of kinetic parameters ( k UV, MP for UV susceptible and k OH, MP for UV resistant probe compounds) have the strongest impact on the model's accuracy. Graphical abstract: Image, graphical abstract